Engineering an electroactive Escherichia coli for the microbial electrosynthesis of succinate from glucose and CO2 - Wu, Zaiqiang; Wang, Junsong; Liu, Jun; Wang, Yan; Bi, Changhao; Zhang, Xueli (Microbial cell factories, 2019)
Electrochemical energy is a key factor of biosynthesis, and is necessary for the reduction or assimilation of substrates such as CO.sub.2. Previous microbial electrosynthesis (MES) research mainly utilized naturally electroactive microbes to generate non-specific products. In this research, an electroactive succinate-producing cell factory was engineered in E. coli T110(pMtrABC, pFccA-CymA) by expressing mtrABC, fccA and cymA from Shewanella oneidensis MR-1, which can utilize electricity to reduce fumarate. The electroactive T110 strain was further improved by incorporating a carbon concentration mechanism (CCM). This strain was fermented in an MES system with neutral red as the electron carrier and supplemented with HCO.sub.3.sup.+, which produced a succinate yield of 1.10 mol/mol glucose--a 1.6-fold improvement over the parent strain T110. The strain T110(pMtrABC, pFccA-CymA, pBTCA) is to our best knowledge the first electroactive microbial cell factory engineered to directly utilize electricity for the production of a specific product. Due to the versatility of the E. coli platform, this pioneering research opens the possibility of engineering various other cell factories to utilize electricity for bioproduction.